Population pharmacokinetics of methylphenidate hydrochloride extended-release multiple-layer beads in pediatric subjects with attention deficit hyperactivity disorder - Teuscher NS; Adjei A; Findling RL; Greenhill LL; Kupper RJ; Wigal S (Dove Medical Press, 2015)
Nathan S Teuscher,1 Akwete Adjei,2 Robert L Findling,3,4 Laurence L Greenhill,5 Robert J Kupper,2 Sharon Wigal6 1PK/PD Associates, Trophy Club, TX, 2Rhodes Pharmaceuticals L.P., Coventry, RI, 3Department of Psychiatric Services and Research, Kennedy Krieger Institute, Baltimore, MD, 4Department of Psychiatry and Behavioral Sciences, Johns Hopkins University, Baltimore, MD, 5Department of Psychiatry, Division of Child and Adolescent Psychiatry, New York State Psychiatric Institute, Columbia University, New York, NY, 6AVIDA Inc., Newport Beach, CA, USA Abstract: A new multilayer-bead formulation of extended-release methylphenidate hydrochloride (MPH-MLR) has been evaluated in pharmacokinetic studies in healthy adults and in Phase III efficacy/safety studies in children and adolescents with attention deficit hyperactivity disorder (ADHD). Using available data in healthy adults, a two-input, one-compartment, first-order elimination population pharmacokinetic model was developed using nonlinear mixed-effect modeling. The model was then extended to pediatric subjects, and was found to adequately describe plasma concentration–time data for this population. A pharmacokinetic/pharmacodynamic model was also developed using change from baseline in the ADHD Rating Scale (ADHD-RS)-IV total scores from a pediatric Phase III trial and simulated plasma concentration–time data. During simulations for each MPH-MLR dose level (10–80 mg), increased body weight resulted in decreased maximum concentration. Additionally, as maximum concentration increased, ADHD-RS-IV total score improved (decreased). Knowledge of the relationship between dose, body weight, and clinical response following the administration of MPH-MLR in children and adolescents may be useful for clinicians selecting initial dosing of MPH-MLR. Additional study is needed to confirm these results. Keywords: population pharmacokinetics, Aptensio XR™, MPH-MLR, methylphenidate